Cellulose and zirconium phosphate composite gel material for dialysis system and preparation method of cellulose and zirconium phosphate composite gel material
By preparing cellulose zirconium phosphate composite gel material, the problem of excessive accumulation of zirconium phosphate materials in the hemodialyzer is solved, efficient ion exchange and stable liquid flow are achieved, and the reusability and mechanical strength of the material are improved.
Patent Information
- Application Number
- CN202411438478.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
AI Technical Summary
Zirconium phosphate materials are easily filled in hemodialyzer with too dense accumulation, too low effective ion exchange area, poor liquid circulation, pressure load and even tube explosion problems.
Cellulose zirconium phosphate composite gel material is used. This material is used to stir the ionic liquid solution of cellulose and the zirconium phosphate material to form a dispersed mixed solution, and then forms a hydrogel or organic gel under the action of a precipitant for use in a dialysis system.
The material is controllable in size, has good biocompatibility, can release captured ions under the action of high concentration saline solution or acid, has good reusability, significantly improves adsorption efficiency, and avoids the possible accumulation and pressure overload problems of layered zirconium phosphate materials in the dialyzer.
Smart Images

Figure CN119504227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a cellulose zirconium phosphate composite gel material for a dialysis system and a preparation method thereof. Background Art
[0002] Hemodialysis is one of the renal replacement therapies used to treat patients with acute and chronic renal failure. During the treatment, the patient's blood is drawn out of the body, filtered through the filter (dialyzer) in the dialysis machine, and then returned to the body. The dialyzer removes waste and excess water from the blood by convection osmosis through a semipermeable membrane, while retaining the nutrients and electrolytes needed by the body. Hemodialysis usually helps maintain electrolyte balance in the body, control blood pressure, reduce toxin accumulation, etc. The frequency and duration of hemodialysis treatment depends on the patient's kidney function and health status, and can be performed several times a week to several hours a day.
[0003] Hemodialysis machines are divided into single-pass type and sorbent type according to the treatment method of dialysate. Traditional hemodialysis machines are single-pass type. The dialysate needs to be freshly prepared using a pure water system and a liquid preparation system. It is limited to use within 24 hours, consumes a lot of energy, and the dialysis process is highly dependent on equipment. In recent years, dialysate regeneration type hemodialysis has become the mainstream development direction of hemodialysis treatment. Since it does not rely on water sources and water treatment systems, the dialysis machine can be miniaturized and portable, making home dialysis and portable hemodialysis machines possible. Dialysate regeneration type hemodialysis uses a dialysate regeneration system to remove harmful components in the dialysis waste liquid through substances such as urease, zirconium phosphate (ZrP), zirconium oxide and activated carbon, and the generated regenerated dialysate is circulated for hemodialysis.
[0004] Zirconium phosphate is a two-dimensional layered compound with special structure and properties. It is often used as an exchange material for acidic inorganic cations. Its ion exchange performance comes from -HPO4 2- H + The adsorption performance is derived from the mutual attraction between the material to be adsorbed and the two-dimensional layered structure. In hemodialysis, zirconium phosphate and its derivatives are used as high-efficiency adsorbents to adsorb and remove ammonium ions (NH 4+). However, filling zirconium phosphate materials in hemodialyzers may lead to over-dense stacking, thereby reducing the effective ion exchange area. In addition, due to the uneven particle size of commonly used zirconium phosphate (200nm-2μm), there is a problem of excessive pressure drop in the adsorption fluid channel. And the spherical particles assembled by zirconium phosphate alone cannot maintain their three-dimensional structure, and are prone to rupture and cause particle overflow under multiple liquid impacts. The tight stacking of layers limits the ion exchange performance of zirconium phosphate materials, and the dosage needs to be increased to improve the adsorption effect, which is contrary to the requirements of lightweight and efficient home hemodialysis or hemodialysis machines. In order to avoid the problems of pressure overload, particle rupture and insufficient actual contact area caused by the over-dense stacking of zirconium phosphate materials in the above-mentioned hemodialyzers, it is urgent to develop a zirconium phosphate composite material to enhance its mechanical strength and specific surface area, and improve its stability and durability in hemodialysis.
[0005] The Chinese patent document with the publication number CN114620698A discloses a large-particle zirconium phosphate and a preparation method thereof, wherein the method comprises mixing carbonate and zirconium oxychloride, heating reaction, generating zirconium carbonate precipitate, filtering to obtain zirconium carbonate; mixing the obtained zirconium carbonate precipitate with an alkaline solution, generating zirconium hydroxide precipitate, filtering to obtain zirconium hydroxide; finally, mixing zirconium hydroxide with phosphoric acid, heating reaction, generating zirconium phosphate precipitate, filtering, washing, and drying to obtain large-particle zirconium phosphate (average diameter of 10-50 microns). The corresponding large-particle zirconium phosphate is used as an ion exchanger, has a large ion exchange capacity, and has a good exchange effect on metal ions. The large-particle zirconium phosphate in the patent is a layered zirconium phosphate, which has an enhanced ion adsorption capacity under stirring, but is not suitable for filling an adsorption column. The layered zirconium phosphate will precipitate quickly in a non-stirring state to form a very dense stacking structure, which will lead to problems such as poor flow of the dialysate and a small effective contact area. Summary of the invention
[0006] In order to solve the problem that zirconium phosphate materials are too densely packed when filled in a hemodialyzer, resulting in too low effective ion exchange area, poor liquid circulation, pressure load and even pipe burst, the present invention provides a method for preparing a cellulose zirconium phosphate composite gel material for a dialysis system. The cellulose zirconium phosphate composite gel material has controllable size and good biocompatibility, can be easily loaded into hemodialyzers of different sizes, is used for dialysate regeneration hemodialysis, can release captured ions under the action of high concentration salt solution or acid, and has good reusability.
[0007] The specific technical solutions adopted are as follows:
[0008] A method for preparing a cellulose zirconium phosphate composite gel material for a dialysis system comprises the following steps:
[0009] (1) preparing an ionic liquid solution of cellulose, and then adding a zirconium phosphate material and stirring to obtain a uniformly dispersed mixed solution; the zirconium phosphate material is α-zirconium phosphate, γ-zirconium phosphate, θ-zirconium phosphate, τ-zirconium phosphate or sodium zirconium phosphate;
[0010] (2) Under the action of a precipitant, the mixed solution of step (1) is formed into a hydrogel or an organogel; and the hydrogel, the aerogel formed after the hydrogel is dried, or the aerogel formed after the organogel is dried is used as the cellulose zirconium phosphate composite gel material in a dialysis system.
[0011] Specifically, the cellulose is natural cellulose, and cotton cellulose, wood cellulose or bacterial cellulose can be selected. The above natural cellulose can be obtained from the market or extracted or synthesized by conventional technical means of those skilled in the art; the ionic liquid is an alkyl imidazole ionic liquid, including 1-methyl-3-butyl imidazole halide, 1-butyl-3-methyl imidazole halide, 1-ethyl-3-methyl imidazole acetate, 1-ethyl-3-methyl imidazole halide, 1-allyl-3-methyl imidazole halide or 1-(2-hydroxyethyl)-3-methyl imidazole halide.
[0012] The present invention first prepares a uniform ionic liquid mixed solution including cellulose and zirconium phosphate materials, and then converts the solute in the mixed solution into a solid phase through the action of a precipitant to form a gel, thereby preparing a large-size hydrogel with controllable shape, a spherical hydrogel particle with controllable size, and a porous large-size aerogel or aerogel particle with high porosity for use in a dialysis system, wherein cellulose is used as a supporting material to construct a three-dimensional network skeleton with controllable size and shape in the composite material. At the same time, zirconium phosphate is uniformly dispersed and embedded in the cellulose network, which increases the contact sites of the zirconium phosphate material during hemodialysis, thereby achieving high throughput and stability.
[0013] Optionally, in the ionic liquid solution of cellulose, the mass ratio of cellulose to ionic liquid is 1:10-100.
[0014] Optionally, in the mixed solution, the mass ratio of cellulose to zirconium phosphate material is 1:0.5-300.
[0015] Preferably, in the mixed solution, the mass ratio of cellulose, ionic liquid and zirconium phosphate material is 1:30-60:2-50. If the proportion of ionic liquid is too low, the viscosity will increase and the cellulose will be difficult to completely dissolve; if the proportion is too high, the prepared gel material may have insufficient mechanical strength and be easy to break. If the proportion of zirconium phosphate is too low, the adsorption effect will be weakened, while if the proportion is too high, the contact between zirconium phosphate and cellulose will be insufficient, which may cause the zirconium phosphate to fall off during the subsequent multiple washing and adsorption processes, increasing the risk of hemodialysis.
[0016] Optionally, cellulose is dispersed in an ionic liquid, heated and stirred at 40-160°C for 5-120 minutes to obtain an ionic liquid solution of cellulose, zirconium phosphate material is added, and heating and stirring at 40-160°C for 5-120 minutes are continued, and an organic solvent is added for solubilization to obtain a uniformly dispersed mixed solution; adding an organic solvent for solubilization can improve the fluidity of the mixed solution, which is beneficial to the preparation of gel particle-type cellulose zirconium phosphate composite gel material.
[0017] Furthermore, the organic solvent is preferably N,N-dimethylformamide, and the volume ratio of the ionic liquid to the organic solvent is 1-10:1. Adding too much organic solvent will affect the formation of hydrogel or organogel.
[0018] The precipitant includes at least one of deionized water, ethanol, methanol, acetone, isopropanol or tert-butanol.
[0019] Optionally, the method for making the mixed solution form a hydrogel or an organogel is method S01 or method S02;
[0020] S01: adding the mixed solution into a mold, cooling it to room temperature, adding a precipitant to remove the ionic liquid, and demolding to obtain a hydrogel or an organogel (conventional gel type, the shape of the hydrogel or organogel depends on the mold);
[0021] S02: placing the mixed solution in a container, and dripping the mixed solution droplets into a precipitant by a granulation method to obtain a hydrogel or organogel in the form of gel particles; the granulation method includes but is not limited to a falling ball method, a coaxial airflow spray method, a microfluidic method or an electrostatic spray method.
[0022] Optionally, in step (2), the drying method is CO2 supercritical drying, freeze drying, forced air drying or heating drying.
[0023] The invention also provides a cellulose zirconium phosphate composite gel material obtained by the preparation method of the cellulose zirconium phosphate composite gel material.
[0024] The cellulose zirconium phosphate composite gel material uses cellulose as a structural unit, and is dissolved and regenerated by ionic liquid to construct a cellulose gel material loaded with zirconium phosphate. In particular, the aerogel material has good mechanical properties and reusability, and has high porosity, which can provide a larger contact specific surface area and more binding sites in hemodialysis, avoiding the accumulation and pressure overload problems that may occur in the layered zirconium phosphate material in the dialyzer, as well as the risk of particle rupture.
[0025] The present invention also provides a device including a dialysis system, wherein the dialysis system includes an adsorption column, and the cellulose zirconium phosphate composite gel material is used as a cation exchange material to fill the adsorption column to achieve adsorption and desorption of ammonium ions.
[0026] Furthermore, the device including the dialysis system is a dialysate regeneration type hemodialysis device, and the cellulose zirconium phosphate composite gel material is a hydrogel of gel particle type or an aerogel formed after the organic gel is dried; the conditions for achieving ammonium ion desorption are: treating the cellulose zirconium phosphate composite gel material adsorbed with ammonium ions with a salt solution or an acid solution to release the adsorbed ammonium ions, thereby completing the regeneration of the cellulose zirconium phosphate composite gel material and improving the application performance and recycling of the zirconium phosphate material in the hemodialyzer.
[0027] Furthermore, the salt solution is at least one of sodium chloride solution, potassium chloride solution, and lithium chloride solution, with a concentration of 1-4M; the acid solution is at least one of hydrochloric acid solution, acetic acid solution, and carbonic acid solution, with a pH of 1-8.
[0028] The size and particle size of the cellulose zirconium phosphate composite gel material are controllable. The large-sized one can be used for static adsorption, and the gel particle type can be loaded into an adsorption column for dynamic adsorption. The cellulose zirconium phosphate composite gel material has a high affinity for ammonium ions (NH4 + ) can reach 60 mg / g within 30 minutes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The cellulose zirconium phosphate composite gel material provided by the present invention has a simple preparation process, good biocompatibility, and a large effective area. Natural cellulose is used as a skeleton structure material to wrap and support the zirconium phosphate material, which can effectively isolate each zirconium phosphate layer and increase its contact area with the dialyzed fluid, thereby significantly improving the adsorption efficiency. In addition, the unique layered structure of the zirconium phosphate material allows ions to diffuse into the interlayer space that is different from the bulk environment, and quickly adsorbs the target ions in the solution through ion exchange. The adsorbed target ions can be released under the action of a high concentration salt solution or an acid solution, thereby realizing the regeneration of the cellulose zirconium phosphate composite gel material. It has good reusability and overcomes the problem of difficult recycling and regeneration.
[0031] (2) The cellulose zirconium phosphate composite gel material provided by the present invention has various forms and controllable sizes, and can be prepared into specific sizes according to the flow rate and flux in actual use conditions, thereby solving the problems of pressure drop and particle leakage in the adsorption fluid channel. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope photograph of the cellulose nanofibers and α-zirconium phosphate in Example 1, A is the cellulose nanofibers, and B is the α-zirconium phosphate.
[0033] Figure 2The cellulose zirconium phosphate composite gels are obtained by different preparation methods. A is the large-sized composite organic gel in Example 1, and B is the spherical composite hydrogel particles injection-molded by the syringe pump in Example 2.
[0034] Figure 3 These are optical pictures of micrometer-sized spherical composite gel particles obtained by electrostatic spraying in Example 3; wherein A is a picture of aerogel particles, and B is an optical microscope picture of a single organogel particle.
[0035] Figure 4 3 is a scanning electron microscope photograph of the zirconium phosphate composite aerogel particles in Example 2, wherein B is an enlarged view of A.
[0036] Figure 5 These are the test results of the ammonium ion adsorption performance of zirconium phosphate composite aerogel particles in different ratios.
[0037] Figure 6 It is a laboratory dialysis column loaded with zirconium phosphate composite aerogel particles of different sizes in Example 2 and Example 3, wherein A is Example 2 and B is Example 3. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the examples and accompanying drawings. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods of the following examples that do not specify specific conditions are usually performed under normal conditions or under conditions recommended by the manufacturer. The content that is not described in detail in this specification sheet belongs to the prior art known to professionals in the field. The experimental materials used in the following examples, if not otherwise specified, can be purchased by conventional biochemical reagent companies.
[0039] The cellulose nanofiber solution is commercially available, wherein the cellulose nanofiber is natural cellulose. The cellulose nanofiber solution is freeze-dried to obtain cellulose nanofibers for later use.
[0040] Example 1
[0041] Weigh 0.2g of cellulose nanofibers and 5g of 1-butyl-3-methylimidazolium chloride into a beaker, heat to 80°C while stirring magnetically, cellulose gradually dissolves in the ionic liquid, 20 minutes later, cellulose is completely dissolved in the ionic liquid, and an ionic liquid solution of cellulose is obtained, and 0.5g of α-zirconium phosphate is added thereto, and heating and stirring are continued for 15 minutes to obtain a uniformly dispersed mixed solution. Pour the prepared mixed solution into a mold while hot, and soak the mold in ethanol after the mixed solution cools to room temperature, and replace the ethanol every 1 hour. After replacing it 3 times, demold the mold to obtain a cellulose zirconium phosphate composite organic gel, and further perform CO2 supercritical drying to obtain an aerogel, and use the aerogel as the cellulose zirconium phosphate composite gel material.
[0042] Weigh 200 mg of aerogel and soak it in 3 ml of 10 mM NH4Cl solution. Let it stand at room temperature for 1 hour. About 50 wt.% NH4 + It was then taken out and transferred to a 0.1M hydrochloric acid solution (pH 1) for 2 hours, and then rinsed with deionized water for multiple times to achieve regeneration. The aerogel can be reused for NH4 + Adsorption.
[0043] Example 2
[0044] Weigh 0.34g of cellulose nanofibers and 12g of 1-ethyl-3-methylimidazole acetate into a beaker, heat to 60°C while stirring magnetically, cellulose gradually dissolves in the ionic liquid, 6 minutes later, cellulose is completely dissolved in the ionic liquid, and an ionic liquid solution of cellulose is obtained, 3.4g of sodium zirconium phosphate is weighed and added thereto, heating and stirring are continued for 20 minutes to obtain a uniformly dispersed mixed solution. The prepared mixed solution is transferred to a syringe while hot, and the mixed solution is dripped into deionized water at a speed of 10ml / min through a precision syringe pump, and the deionized water is replaced every 0.5 hours. After 4 replacements, the collected gel particle-type cellulose zirconium phosphate composite hydrogel is freeze-dried to obtain an aerogel, and the aerogel is used as the cellulose zirconium phosphate composite gel material.
[0045] 100 mg of aerogel was weighed and immersed in 2 ml of 20 mM NH4Cl solution and allowed to stand at room temperature for 30 minutes. The NH4Cl solution was about 78 wt.%. + It was then taken out and transferred to a 4M sodium chloride solution to soak for 1 hour, and then rinsed with deionized water several times to achieve regeneration. The aerogel can be reused for NH4 + Adsorption.
[0046] Example 3
[0047] Weigh 0.5g of cellulose nanofibers and 20g of 1-allyl-3-methylimidazolium chloride into a beaker, heat to 90°C while stirring magnetically, cellulose gradually dissolves in the ionic liquid, 30 minutes later, cellulose is completely dissolved in the ionic liquid, and an ionic liquid solution of cellulose is obtained, 2g of γ-zirconium phosphate and 2g of DMF are weighed and added thereto, heated and stirred for 10 minutes, and a uniformly dispersed mixed solution is obtained. The prepared mixed solution is transferred to a syringe while hot, and the mixed solution is sprayed into isopropanol by electrostatic spraying, and the isopropanol is replaced every 0.5 hours. After 4 replacements, the collected gel particle-type cellulose zirconium phosphate composite organic gel is air-dried overnight at room temperature, and then thoroughly dried in an oven to obtain an aerogel, and the aerogel is used as the cellulose zirconium phosphate composite gel material.
[0048] Weigh 600 mg of aerogel and load it into a dialysis column. Add 1 ml of a mixed solution of 25 mM NH4Cl and 150 mM NaCl from the top of the dialysis column to simulate the ammonium adsorption capacity of the cellulose zirconium phosphate composite gel material in a physiological salt concentration environment. The dialysis process takes about 20 minutes, and about 92 wt.% of NH4 + was adsorbed; the dialysis column was then rinsed with 5 ml of 4M sodium chloride solution and deionized water respectively to achieve regeneration of the dialysis column.
[0049] Sample analysis
[0050] (1) Morphology analysis
[0051] Figure 1 This is a scanning electron microscope photograph of the cellulose nanofibers and α-zirconium phosphate in Example 1, wherein A is cellulose and B is α-zirconium phosphate with a diameter of 1-2 microns.
[0052] Figure 2 These are optical pictures of the cellulose zirconium phosphate composite gels prepared in Examples 1 and 2, wherein A is Example 1, and B is Example 2. The method of Example 2 obtains a gel particle-type hydrogel.
[0053] Figure 3 This is an optical picture of the spherical composite gel particles prepared in Example 3, wherein A is a macroscopic morphology of the aerogel particles, and B is an optical microscope picture of a single organic gel particle. The size of the gel particles can be controlled by adjusting the positive and negative voltages and the flow rate. The size of the organic gel particles prepared in Example 3 is 600-900 microns.
[0054] Figure 4 3 is a scanning electron microscope photograph of the zirconium phosphate composite aerogel particles in Example 2, wherein B is an enlarged view of A. It can be seen from the figure that the zirconium phosphate is uniformly dispersed in the network structure of cellulose.
[0055] (2) Analysis of ammonium ion exchange performance
[0056] Figure 5 The performance test results of different aerogels prepared to adjust the ratio of cellulose and zirconium phosphate in 4 hours for adsorbing ammonium ions according to the method of Example 2 show that when the mass ratio of cellulose and zirconium phosphate is 1 / 2, the ammonium ion exchange rate is about 70% of that of pure zirconium phosphate under the same mass. As the content of zirconium phosphate increases, the adsorption effect increases. When the mass ratio of cellulose and zirconium phosphate is 1 / 10, 1 / 100, and 1 / 250, the ammonium ion exchange rate increases slightly under the same conditions. However, after long-term immersion, the cellulose zirconium phosphate composite gel material (1 / 250, 1 / 100) with a relatively high proportion of zirconium phosphate will have some zirconium phosphate fall off the particles, which is not conducive to subsequent regeneration and collection.
[0057] Figure 6 These are optical images of cellulose zirconium phosphate composite gel materials with aerogels of different sizes loaded into dialysis columns of different sizes. The size of the aerogel particles in A is larger than that in B.
[0058] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a cellulose zirconium phosphate composite gel material for a dialysis system, characterized in that: The following steps are involved: (1) preparing an ionic liquid solution of cellulose, and then adding a zirconium phosphate material and stirring to obtain a uniformly dispersed mixed solution; the zirconium phosphate material is α-zirconium phosphate, γ-zirconium phosphate, θ-zirconium phosphate, τ-zirconium phosphate or sodium zirconium phosphate; (2) Under the action of a precipitant, the mixed solution of step (1) is formed into a hydrogel or an organogel; and the hydrogel, the aerogel formed after the hydrogel is dried, or the aerogel formed after the organogel is dried is used as the cellulose zirconium phosphate composite gel material in a dialysis system.
2. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: The cellulose is natural cellulose; the ionic liquid is an alkyl imidazole ionic liquid, including 1-methyl-3-butyl imidazole halide, 1-butyl-3-methyl imidazole halide, 1-ethyl-3-methyl imidazole acetate, 1-ethyl-3-methyl imidazole halide, 1-allyl-3-methyl imidazole halide or 1-(2-hydroxyethyl)-3-methyl imidazole halide.
3. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: In the cellulose ionic liquid solution, the mass ratio of cellulose to the ionic liquid is 1:10-100; in the mixed solution, the mass ratio of cellulose to the zirconium phosphate material is 1:0.5-300.
4. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: The cellulose is dispersed in the ionic liquid, heated and stirred at 40-160°C for 5-120 minutes to obtain a cellulose ionic liquid solution, and then the zirconium phosphate material is added and continued to be heated and stirred at 40-160°C for 5-120 minutes, and an organic solvent is added for solubilization to obtain a uniformly dispersed mixed solution.
5. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: The precipitant includes at least one of deionized water, ethanol, methanol, acetone, isopropanol or tert-butanol.
6. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: The method for making the mixed solution form a hydrogel or an organogel is selected from method S01 or method S02; S01 adding the mixed solution into a mold, cooling it to room temperature, adding a precipitant to remove the ionic liquid, and demolding to obtain a hydrogel or an organogel; S02: placing the mixed solution in a container, and dripping the mixed solution droplets into a precipitant by a granulation method to obtain a gel particle-type hydrogel or organogel.
7. The method for preparing the cellulose zirconium phosphate composite gel material according to claim 1, characterized in that: In step (2), the drying method is CO2 supercritical drying, freeze drying, forced air drying or heating drying.
8. A cellulose zirconium phosphate composite gel material obtained according to the method for preparing a cellulose zirconium phosphate composite gel material according to any one of claims 1 to 7.
9. A device comprising a dialysis system, characterized in that The dialysis system comprises an adsorption column, and the cellulose zirconium phosphate composite gel material according to claim 8 is used as a cation exchange material to fill the adsorption column to achieve adsorption and desorption of ammonium ions.
10. The device according to claim 9, characterized in that The device including the dialysis system is a dialysate regeneration type hemodialysis device; the conditions for achieving ammonium ion desorption are: treating the cellulose zirconium phosphate composite gel material adsorbed with ammonium ions with a salt solution or an acid solution to release the adsorbed ammonium ions and complete the regeneration of the cellulose zirconium phosphate composite gel material.
Citation Information
Patent Citations
Large-particle zirconium phosphate and preparation method thereof
CN114620698A